The "Ambivalence of the Sacred" in Africa: The Impact of Religion on Peace and Conflict in Sub-Saharan Africa - Matthias Basedau; Alexander de Juan (German Institute of Global and Area Studies (GIGA), 2008)
Given the widespread focus on socioeconomic factors, it comes as no surprise that religion is neglected in most theoretical explanations of African civil conflicts. While scholarly interest is increasing in light of the civil wars in Sudan, Nigeria, and northern Uganda, no systematic empirical analysis has been undertaken to date. Hence, this paper aims to provide a preliminary assessment of the role of religions in sub-Saharan civil conflicts. Quantitative and qualitative analysis based on a newly compiled database including 28 violent conflicts show that religion plays a role more frequently than is usually assumed and that the effects of religions are principally ambiguous. Religious actors and institutions have escalating effects in many cases, yet more often they become active for peace. Religious identities and ideas seem to have a particular impact on conflict. Even though religion seems secondary when compared to classical 'risk factors', the findings demonstrate that religious factors have to be taken seriously when analyzing civil conflicts in Africa. – – Der Fokus auf sozioökonomischen Faktoren lässt in den meisten Erklärungsansätzen afrikanischer Gewaltkonflikte keinen Raum für den Faktor Religion. Wenngleich das Interesse an seiner Wirkung angesichts der Bürgerkriege im Sudan, in Norduganda und Nigeria gestiegen ist, bleiben systematische Analysen bislang weitestgehend aus. Zur Schließung dieser Lücke versucht das vorliegende Working Paper beizutragen, indem es eine erste, vorläufige Einschätzung der Rolle von Religionen in Gewaltkonflikten im subsaharischen Afrika vornimmt. Quantitative und qualitative Analysen unter Nutzung einer neu erstellten Datenbasis, die bislang 28 Gewaltkonflikte in Afrika umfasst, zeigen, dass Religionen und religiöse Unterschiede in weitaus mehr Fällen eine bedeutende Rolle spielen als gemeinhin angenommen. Der Einfluss religiöser Faktoren ist grundsätzlich ambivalent: In vielen Konflikten tragen religiöse Akteure und Organisationen zur Eskalation der Auseinandersetzung bei; noch häufiger jedoch versuchen sie, sich für eine friedliche Lösung einzusetzen. Dabei scheinen sich vor allem religiöse Identitäten und Inhalte auf die Ausprägung verschiedener Konfliktvariablen auszuwirken. Wenngleich die Wirkung dieser religiösen Faktoren im Vergleich zu klassischen Risikofaktoren sekundär scheint, verdeutlichen die Befunde die Notwendigkeit, den Faktor Religion bei der Analyse afrikanischer Bürgerkriege ernst zu nehmen.
Keywords: 300; religion; Africa; ambivalence; civil war; violent conflict